ANALISIS MANAJEMEN RISIKO PADA KAWASAN TAMAN NASIONAL GUNUNG GEDE PANGRANGO (TNGGP) JAWA BARAT - Suroso Suroso (Jurnal Bina Akuntansi, 2018)
Tourism has already become major economic contributor since 2014. Many people start to get the experience and explore the world. Base on WTO prediction, there are about 1.6 billion tourists over the world, and most of them are in Asia and Pasific. By 2020 these people could generate about 2 trilion USD income in tourism sector. Indonesia has known as one of biggest archipelago island in the world and has a lot of tourist spot over their island. One of interesting spot in West Java is Taman Nasional Gunung Gede Pangrango in Bogor. This place has been well known as agri-tourism spot for long time ago. Unfortunately in order to increase the competitiveness of this tourist spot, they should implement risk management in their daily operational. We found that the management hasn’t implement any risk management in their daily operational. So we would like to conduct some observation and hope can mapping potential risk of this place. Purpose of this research is aim to mapping risk and conducted quadran analysis in order to achieved good risk management of Taman Nasional Gunung Gede Pangrango. And the this tourist spot can be one of unique tourist spot that can support Indonesia Tourism in 2020.